Degradation of Atenolol with Electrochemical Oxidation at Mixed Metal Oxide Electrodes Assisted by UV Photolysis. Issue 4 (12th February 2018) - Zhu, Shumin; Dong, Bingzhi; Zhou, Shiqing
Abstract : Electrochemical oxidation has drawn considerable research attention for the destruction of organic contaminants. This study utilizes the combination of electrolysis and the UV photolysis process to degrade the β‐blocker atenolol (ATL). The results show that the combination of electrolysis and UV photolysis is superior to a single process alone based on the removal rates of ATL and electrical efficiency per order (EE/O). In situ electrogenerated chlorine is confirmed to be responsible for ATL degradation with NaCl electrolytes, and mixed metal oxide (MMO) anodes play a more significant role in the generation of active chlorine than platinum (Pt) anodes. Moreover, reactive species (hydroxyl radical OH and chlorine radical Cl) mainly contributed to ATL degradation during the photo‐electrolysis process. Increasing the concentration of NaCl electrolytes and applied current densities can enhance the ATL degradation. Finally, major intermediate products are identified, and a possible degradation pathway of ATL is proposed during the photo‐electrolysis processes. This study demonstrate that the photo‐electrolysis process can be considered as a potential technology for the destruction of pharmaceutical pollutants in water. Abstract : Degradation of the β‐blocker atenolol (ATL) is evaluated by a combination of electrolysis and UV photolysis. The results indicate that the reactive species (hydroxyl radical OH and chlorine radical Cl) mainly contributed to ATL degradation during the photo‐electrolysis process. This study provides a potential technology to enhance the removal of pharmaceutical pollutants from aqueous solution.